Study on fused/cast AZS refractories for deployment in vitrification of radioactive waste effluents - Sengupta, Pranesh; Mishra, Raman K.; Soudamini, N.; Sen, D.; Mazumder, S.; Kaushik, Chetan P.; Ajithkumar, Thalasseril G.; Banerjee, K. (Journal of Nuclear Materials, 2015)
Fused/cast Al2O3-ZrO2-SiO2 (FC-AZS)' is being considered as `glass contact refractory' within ceramic melters, to be used for nuclear waste immobilization. Microstructural analyses reveal random distributions of baddeleyite (ZrO2) within aluminosilicate (Al2SiO5) matrix. Al-27 and Si-29 NMR data suggest that within aluminosilicate matrix Al occurs in both 4- and 6-fold co-ordinations whereas Si prefers a 4-fold environment. Polydispersity of pores has been studied with small-angle neutron scattering (SANS) technique. Corrosion rates of FC-AZS within 6 M HNO3, simulated wastes (500 h exposure), and borosilicate melt (975 degrees C, 800 h exposure) are found to be 0.38 x 10(3) mu my(-1), 0.13 x 10(3) mu my(-1) and 4.75 x 10(3) mu my(-1) respectively. A comparison of chemical interaction data clearly suggests that FC-AZS exhibits better chemical durability than AZC refractory (Al2O3-ZrO2-Cr2O3, also used for similar purpose). Thermal cycling studies indicate that FC-AZS retains structural integrity (including compressive strength and density) even up to 20 cycles. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Interaction between refractory material and hazardous liquid; Nuclear waste immobilization; Vitrification melter

Vanadium in borosilicate glass - Sengupta, Pranesh; Dey, Krishna K.; Halder, Rumu; Ajithkumar, Thalasseril G.; Abraham, Geogy; Mishra, Raman K.; Kaushik, Chetan P.; Dey, Goutam K. (Journal of the American Ceramic Society, 2015)
Understanding the role of V2O5 within borosilicate glass matrices is important for the development of novel matrices toward immobilization of sulfate containing high-level nuclear wastes. Present investigation shows, within sodium barium borosilicate glass matrix V2O5 can be homogeneously added up to 5mol% and beyond which it separates out into three phases, for example, (i) silica (ii) Barium (Ba) - Vanadium (V) oxide, and (iii) glass matrix. Si-29 MAS NMR (Nuclear Magnetic Resonance) studies of the samples show that below 5mol% V2O5 addition, silicate network is dominantly constituted of Q(2) and Q(3) structural units, whereas above this, the network gets more polymerized through formation of Q(3) and Q(4) units. In case of borate network, B-11 MAS NMR investigations revealed that the concentration of BO4 [(0B, 4Si)] unit increases gradually up to 5mol% and then it decreases at the cost of BO4 [(1B, 3Si)], BO3 (symmetric) and BO3 (asymmetric) units. Micro-Raman analyses of the samples showed that with additions of V2O5 in diluted concentrations, amorphous silicate network remained unaltered, whereas some amplification in signals corresponding to ring-type metaborate and VO5 units exists. It is therefore apparent from both MAS-NMR and micro-Raman studies that with V2O5 additions within the solubility limit (5mol%), borate network gets depolymerized leading to decrease in hardness from an average value of 5.0-4.2GPa.